Does Islamic Banking Contribute to Economic Growth and Industrial Development in Turkey? - Yüksel, Serhat; Canöz, İsmail (IKONOMIKA, 2017)
This paper aims to identify the effects of Islamic banking on economic growth and industrial development in Turkey. For this purpose, quarterly data for the periods between 2005 and 2016 were taken into the consideration. Additionally, VAR Granger causality analysis was used in this study. It was concluded that Islamic banks’ loans do not have a significant effect on the improvement of economy and industry in Turkey. The main reason for this result is that Islamic banking has a very low percentage in Turkish banking sector. Thus, it can be said that Islamic banking in Turkey should be so developed that it can contribute to GDP growth and industrial development.